(untitled) - Matthews, Kent (Hoboken, N.J., 2014)
The Economics of Banking describes and explains thebehaviour of banks by examining trends and operations in bankingwithin a mathematically accessible microeconomic framework. Thisnew 3rd edition has been fully revised and updated toreflect the major changes that have taken place in the bankingsector and many new topics including new coverage of Islamicbanking. This accessible and user-friendly textbook is essential readingfor final year undergraduate and postgraduate students takingcourses in banking.
Kinh tế học tài chính và ngân hàng
Keywords: Ngân hàng,Banks and banking